Hubungan Kadar Cancer Antigen 15-3 Serum dengan Metastasis Kanker Payudara - Fakhriyyatur Rahmi M; Rikarni Rikarni; Nora Harminarti (Fakultas Kedokteran, Universitas Andalas, 2021)
Background: CA 15-3 serum is one of the tumor marker that has been recommended by American Soviety of Clinical Oncology to show the response of the therapy, prognosis and metastasis of the breast cancer. CA 15-3 serum is a mucin that will be expressed by breast cancer cell. The over expression of CA 15-3 serum can be occurred if the cell progressivity is increase. Several studies have shown that CA 15-3 serum is increasing in metastasis breast cancer. Objective: This study aimed to determine the relationship between the CA 15-3 serum with metastasis breast cancer. Methods: This study used a cross sectional design in breast cancer patient at Dr. M Djamil Hospital. Sampling using consequtive sampling technique with a total sample of 46 people. Data was analyzed by using Mann-Whitney test. Results: Distant metastasis of Breast cancer was more common in age group of 40-60 years (65,21%) and 86,96% had shown a lymphatic metastasis. The mean of CA 15-3 serum was higher in the group with distant metastasis 385,0439 U/mL compared to group without distant metastasis. Distant metastasis was more common in single state metastasis (69,6%) with the mean 472,24 U/mL. Common targeting organ of the distant metastasis was lung (69,9%). The highest mean of CA 15-3 serum was in pleura 557,2 U/mL. Conclusion: There was a statistically significant relationship between the mean of CA 15-3 serum with metastasis breast cancer (p=0.000).